Retrospective analysis of hospitalization rates in patients with schizophrenia 12 months before and 12 months after the switch to once-monthly long-acting injectable paliperidone palmitate - Totić Poznanović, Sanja; Marković, Miloš (Vojnosanitetski pregled, 2023)
Background/Aim. There is no available published data about the use of long-acting injectable paliperidone palmitate (PP) in schizophrenia patients in the Republic of Serbia. The aim of this study was to assess hospitalization rates before and after the switch to once-monthly long-acting injectable PP in schizophrenia patients, as well as their compliance with this drug. Methods. We conducted a retrospective cross-sectional study in which hospitalization rates were evaluated 12 months before and 12 months after the switch to once-monthly long-acting injectable PP in 113 schizophrenia patients. The age of the enrolled patients was between 18 and 66 years. Results. The average age of the enrolled patients was 38.36 ± 11.62 years. Among them, 77 (68.1%) were male, and 36 (31.9%) were female. Out of the total number of 113 patients treated with once-monthly injectable PP, 78 (69.03%) were on monotherapy, while 35 (30.97%) had one additional oral antipsychotic (risperidone, olanzapine, aripiprazole, or clozapine). Out of the total number of 113 patients, 68 (60.18%) were not hospitalized in the 12-month period before the switch to once-monthly long-acting injectable PP, while 45 (39.82%) were hospitalized in the same period. Given that 8 patients out of the total number of 113 were excluded from therapy due to an adverse event or their own decision in the period after the switch to PP, the analysis of the hospitalization rate after the switch to PP was performed for the remaining 105 patients, of which 9 (8.57%) were hospitalized in the period after the switch to PP, and 96 (91.43%) were not. Conclusion. Our results show high compliance in the treatment with once-monthly injectable PP and a positive impact of treatment with this drug on low hospitalization rate in a 12-month period in patients with schizophrenia. Considering the availability of this drug in the Republic of Serbia, these results encourage the use of once-monthly injectable PP as an important therapeutic option in schizophrenia patients.
Keywords: antipsychotic agents; delayed-action preparations; drug-related adverse effect and adverse reactions; hospitalization; paliperidone palmitate; patient compliance; schizofrenia; serbia